The peritonsillar abscess and its management – is incision and drainage only a makeshift to the tonsillectomy or a permanent solution? - Ketterer, Manuel Christoph; Maier, Maren; Burkhardt, Valentin; Mansour, Naglaa; Knopf, Andreas; Becker, Christoph (Frontiers in Medicine, 2023)
Introduction: This study aims to examine the long-term management of peritonsillar abscess and compare needle aspiration, incision with drainage, and tonsillectomy in terms of comorbidities, complication rates, and recurrences in the largest study cohort published to date. Methods: We conducted a retrospective analysis of patients, both adults and children, who were treated for peritonsillar abscess between 2007 and 2019. Patient charts were analyzed to assess surgical treatment, infection and inflammation rates, risk of bleeding, recurrence rates, duration of illness, and sick certificates. Additionally, patient imaging and blood levels were compared. Postal questionnaires were sent to all patients to evaluate subjective success rates, complications, and long-term benefits of the different treatment regimens. General practitioners and ENT doctors in private practices were contacted to gather missing data on the long-term course of the disease. Results: A total of 821 patients with peritonsillar abscess were included in this study. Two patients had to be excluded due to incidental pathological findings. Of the remaining 819 patients, 180 were successfully treated with needle aspiration or incision. Among these patients, 37.7% required tonsillectomy during the same inpatient stay. Laboratory parameters such as leukocyte count or C-reactive protein levels were not indicative of the need for tonsillectomy. Furthermore, computed tomography was only necessary in cases of suspected parapharyngeal abscess, not in clear cases of peritonsillar abscess. Among the 641 patients who underwent tonsillectomy, 11.4% experienced postoperative bleeding requiring treatment. Only patients who underwent bilateral tonsillectomy reported recurrent episodes of sore throat and pharyngitis resulting in absence from work. The ipsilateral recurrence rate for peritonsillar abscess after needle aspiration or incision was 2.8%. There were no contralateral recurrences during the observation period. Conclusion: Due to the lower risk of postoperative bleeding, shorter absence from work, and shorter inpatient stay, incision and drainage are the preferable treatment for peritonsillar abscess. Additionally, patients who underwent bilateral tonsillectomy reported higher rates of work incapacity due to sore throat caused by pharyngitis. No patient met the clear indication for bilateral tonsillectomy due to recurrent acute tonsillitis. The recurrence rate after drainage without tonsillectomy was very low (2.8% ipsilaterally, no recurrence contralaterally).